KRISIS EKSISTENSI BAHASA JAWA KRISIS EKSISTENSI BAHASA JAWA PADA GENERASI ALFA: STUDI KASUS PESERTA DIDIK SDN MODONG KECAMATAN TULANGAN - FIRA RAHMAH AFIDA FIRA (Jurnal Primary (Kajian Ilmu Pendidikan Dasar dan Humaniora), 2022)
This study aims to describe the use of Javanese in the alpha generation of elementary school age at SD Negeri Modong grade 1 and to describe the factors causing the decline in the existence of the alpha generation of elementary school age in Javanese. This study uses qualitative research. Collecting data in this article using a questionnaire, participant observation and interviews. The results showed that there was a crisis in the existence of the Javanese language in the alpha generation as indicated by language changes or adjustments. There are two factors causing the crisis of the existence of the Javanese language, namely internal factors and external factors. Internal factors are influenced by psychological factors and the choice of language in the family. While external factors are influenced by family age factors, domicile factors or the area where the family lives, the use of Indonesian as the language of instruction, the age factor of a teacher, technological factors and social factors or the child's social environment